(untitled) (American Journal of Islam and Society, 2011)
Although Wissenschaft des Judentums was the brainchild of German Jews, it reflected the aims of European Jews in general. As noted by the late Professor Amos Funkenstein, “even if we grant that the majority of traditional Jews in France, Austria, and Germany were not aware of the full scope of the achievements of the Wissenschaft, its results nevertheless faithfully reflected the desires and self-image of nineteenth-century Jews craving for emancipation, the mood of the “perplexed of the times.”1 The period of the Enlightenment did little to change the lot of the Jew: he was still seen by many as a Christ-killer, his identity linked to a particular nation—and he could, therefore, never be fully accepted as part of any other national entity. Although some Jews may have become totally assimilated and even converted to Christianity, the general perception was that the Jews wanted to be conditional citizens: while adopting the culture of the environment, they wanted to preserve their special nature as a subculture ...